3x + 4 = 5x - 6 -3x -3x 4 = 2x - 6 +6 +6 10 = 2x 5 = x
So -3x - 6 = x - 4, ie -2 = 4x so x = -½ and y = -4½
3x = x + 4 x = 2 3x2=6 2+4=6
x=6
-3x -4=2 add four to both sides -3x=6 divide by (-)3 on both sides x= -2 to check: -2(-3) -4=2 6-4=2 It checks.
5x - 4 = 3x + 6 5x - 3x = 6 + 4 2x = 10 x = 5
If: 3x+6 = 18 Then: x = 4
3x + 4 = 5x - 6 -3x -3x 4 = 2x - 6 +6 +6 10 = 2x 5 = x
Solve:4 - 3x = 104 - 3x - 4 = 10 - 4-3x = 6-3x/-3 = 6/-3x = -2Check:4 - (3 x -2) = 104 - (-6) = 104 + 6 = 1010 = 10
-3x+14 = -4 -3x = -4-14 -3x = -18 x = 6
"2 over 3x equals 4" is an equation in a single variable, x.2/(3x) = 4 => 3x/2 = 1/4 => 3x = 2/4 = 1/2 => x = 1/6.
So -3x - 6 = x - 4, ie -2 = 4x so x = -½ and y = -4½
-3x - 2 = -6 -3x = -6 + 2 -3x = -4 -x = -4/3 x = 4/3 The absolute value is therefore 4/3.
3x+4 = 5x-6 3x-5x = -6-4 -2x = -10 x = 5
T = 3x + 7y; x = 4; y = 6T = 3x + 7y (substitute 4 for x, and 6 for y)T = 3(4) + 7(6) = 12 + 42 = 54
3x = x + 4 x = 2 3x2=6 2+4=6
6 - 3x = 4 - 2x 6 = x + 4 x = 2 Check it. 6 - 6 = 4 - 4 It checks.